2014
DOI: 10.15294/jbat.v3i2.3698
|View full text |Cite
|
Sign up to set email alerts
|

Pemanfaatan Limbah Sekam Padi Menjadi Silika Gel

Abstract: AbstrakSekam padi merupakan salah satu sumber penghasil silika terbesar, berpotensi sebagai bahan pembuatan silika gel. Abu sekam padi mengandung silika sebanyak 87%-97% berat kering. Sintesis silika gel dari abu sekam padi dilakukan dengan mereaksikan abu sekam padi menggunakan larutan NaOH 1N pada suhu 800C selama 1 jam dan dilanjutkan dengan penambahan larutan asam hingga pH=7. Gel yang dihasilkan selanjutnya didiamkan selama 18 jam kemudian dikeringkan pada suhu dikeringkan menggunakan oven pada suhu 800C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
25

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 3 publications
1
24
0
25
Order By: Relevance
“…It was also found that teak wood scraps had more organic compound than rice husks. It could be caused by the fact that rice husks are mostly composed by silica at around 87-97% (Handayani et al, 2014;Trivana et al, 2015).…”
Section: Results and Discussion Rice Husks And Teak Wood Scraps Charamentioning
confidence: 99%
“…It was also found that teak wood scraps had more organic compound than rice husks. It could be caused by the fact that rice husks are mostly composed by silica at around 87-97% (Handayani et al, 2014;Trivana et al, 2015).…”
Section: Results and Discussion Rice Husks And Teak Wood Scraps Charamentioning
confidence: 99%
“…This fact suggests that SCGA washing using various HCl concentrations should be applied to achieve minimum contents of impurities. The silica extraction process was conducted using NaOH solution and then precipitated using HCl solution, adapting from the literature [14]. These mechanisms can be expressed by Equations 1 and 2 [15].…”
Section: Resultsmentioning
confidence: 99%
“…Metode pemisahan yang sering digunakan untuk memisahkan silika pada suatu bahan yaitu ekstraksi. Penelitian yang telah dilakukan terkait metode pemisahan ekstraksi yaitu ekstraksi pada abu sekam padi pada pembuatan nanosilika gel [9], ekstraksi alkali pada limbah sekam padi [10], ekstraksi Fitri, dkk./ Jurnal Teknik Kimia dan Lingkungan, Vol. 5, No.…”
Section: Pendahuluanunclassified